The impact of U.S. refugee policy change & political rhetoric on nonprofit service providers' emotional well-being. Issue 2 (3rd April 2021) - Wathen, Maria V.; Decker, Patrick L.F.; Weishar, Charity N.
ABSTRACT: This study examines how U.S. refugee policy changes from 2014 to 2018 affected the emotional well-being of nonprofit service providers. Participants identified the general political climate, including funding cuts; the Trump administration refugee bans ; the unpredictable nature of policy change; and most impactful, negative political rhetoric, as affecting their emotional well-being. Negative effects on emotional well-being included an increase in stress, anger, sadness, despair, depression, helplessness, and caution. Negative rhetoric also impacted professional identities and personal relationships. Positive effects include greater motivation for advocacy. Impact on emotional well-being differed by level of organization at which the participant worked and by organizational characteristics.